Development of Augmented Reality Media to Improve Student Understanding of Optical Eyes System Materials - Widiasih Widiasih; Zakirman Zakirman; Ratna Ekawati (Jurnal Penelitian Pendidikan IPA, 2023)
Optical material is material that is quite difficult for students because it has abstract concepts. Media that is considered an alternative solution is augmented reality. AR provides an effective learning experience because it displays 3D images so that it is easily accepted by students and makes students interested in learning. This study aims to develop augmented reality media to increase students' understanding of the eye optical system material. The type of research to be carried out in Research and Development, with the chosen development model being ADDIE. Product evaluation is carried out based on test results and product implementation. The population of this research is students of the Physics Education Study Program, FKIP UT, who are enrolled in the 2021.2-semester lectures and tutors for the Physics Education Study Program, FKIP UT. The research sample was students of the UT FKIP Physics Education Study Program who attended several 18 people (from UPBJJ UT Bogor, Jakarta, and Serang and tuweb tutors for the optics course). The data collection method consisted of administering a questionnaire. To determine the level of understanding of student material on system material eye optics, test results given to students were analyzed descriptively. Questionnaire analysis from tutors and students regarding the need for AR media was analyzed descriptively and quantitatively. The sampling technique used was random sampling, in which the entire population has the same rights and opportunities to be involved in research Based on the results of the needs analysis, it shows that 81% of students agree and need AR media to study the optical system of the eye, 72% of students agree that the material for the optical system of the watch has the potential to cause misconceptions if studied without using media. Based on the results of the needs analysis, consists of 3 main topics, namely regarding the structure of the eye, the process of seeing in the eye, and eye defects. The results of the trial analysis using AR media used a paired sample t-test to see the effectiveness of AR media. The results of the analysis of the paired sample t-test showed a Sig.2 tailed value > 0.05 so it can be concluded that there was a significant difference between before and after using AR media. In other words, it is easier for students to understand the material after being treated in the form of AR media on the concept of eye optics.